2015
DOI: 10.1136/bcr-2015-211681
|View full text |Cite
|
Sign up to set email alerts
|

Combined laparoscopic-assisted nephrectomy and complete mesocolic excision for synchronous renal and colon cancers

Abstract: Cancers of the colon and kidney are common malignancies, however, the occurrence of primary synchronous neoplasms of these two organs is uncommon. To the best of our knowledge, this is the first case report of a laparoscopic radical left nephrectomy and extended right complete mesocolic excision (CME) for a patient with synchronous renal and colon cancers. While a radical nephrectomy has long been the standard of care for a renal malignancy, CME has only recently been used. Combined surgeries provide the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Benefits of simultaneous surgery include decreased hospital stay, less postoperative pain and morbidity, early return to work [ 15 ]. Performing a second surgery for synchronous cancers prevents the initiation of adjuvant chemotherapy until both procedures are completed.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of simultaneous surgery include decreased hospital stay, less postoperative pain and morbidity, early return to work [ 15 ]. Performing a second surgery for synchronous cancers prevents the initiation of adjuvant chemotherapy until both procedures are completed.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Veenstra et al 6 and O'Sullivan et al 7 reported feasible simultaneous laparoscopic surgery on the contralateral side of the abdomen. The present report describes two cases of ipsilateral and contralateral abdominal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Combined kidney and colorectal surgery provides an early post-operative recovery and decreased morbidity when associated with laparoscopic approach. Moreover, combined procedures in laparoscopic surgery consent to reduce the risk of pulmonary and cardiac burden related to a single anesthesia instead of two, to obtain an earlier return to work activities and better cosmetic result, in addition to a better cost-effective due to more efficient use of hospital beds [10,27]. Simon et al reported their experience with 5 cases of synchronous laparoscopic resection of colorectal cancer and renal or adrenal mass.…”
Section: Discussionmentioning
confidence: 99%